2010
DOI: 10.1093/humrep/deq093
|View full text |Cite
|
Sign up to set email alerts
|

Previous reproductive history and post-natal family planning among HIV-infected women in Ukraine

Abstract: BACKGROUNDUkraine has the highest antenatal HIV prevalence in Europe. The national prevention of mother-to-child transmission (MTCT) programme has reduced the MTCT rate, but less attention has been given to the prevention of unintended pregnancy among HIV-positive women. Our objectives were to describe the reproductive health, condom use and family planning (FP) practices of HIV-positive childbearing Ukrainian women and to identify factors associated with different methods of post-natal contraception.METHODSHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…However, among SSA women, the rates of contraceptive use are high compared to the observed rates in their country of birth [23], suggesting a rapid acculturation after migration to local contraception patterns. Consistent with previous studies across a range of countries [24][25][26][27][28], the distribution of contraceptive methods differs markedly among HIV-positive women compared to the general population, with a large predominance of condom use among HIV-positive women and a very low rate of use of highly effective methods, including either oral hormonal contraception or the IUD. The proportion of women reporting both HEC and condom as a contraception method was small and in the same range as reported in other western countries: 8.8% in the VESPA2 study, 12% in a convenience sample of European women [12] and 16% of adolescent and young HIV-positive women in the United States [29].…”
Section: Discussionsupporting
confidence: 84%
“…However, among SSA women, the rates of contraceptive use are high compared to the observed rates in their country of birth [23], suggesting a rapid acculturation after migration to local contraception patterns. Consistent with previous studies across a range of countries [24][25][26][27][28], the distribution of contraceptive methods differs markedly among HIV-positive women compared to the general population, with a large predominance of condom use among HIV-positive women and a very low rate of use of highly effective methods, including either oral hormonal contraception or the IUD. The proportion of women reporting both HEC and condom as a contraception method was small and in the same range as reported in other western countries: 8.8% in the VESPA2 study, 12% in a convenience sample of European women [12] and 16% of adolescent and young HIV-positive women in the United States [29].…”
Section: Discussionsupporting
confidence: 84%
“…The Ukraine Post Natal Cohort Study of HIV-Infection Childbearing Women was established in 2007 11. Data reported in 2010 among the cohort of 371 women estimated that 21% of this group were not using contraception in the postnatal period, which is similar to the present population group.…”
Section: Discussionsupporting
confidence: 59%
“…In our adjusted analyses we found that HSV-2 seropositive women were more likely to have a history of pregnancy termination, which may be a marker of greater sexual risk, including lack of or inconsistent use of barrier contraception. In this population, condoms are the main form of contraception [ 23 ] which is an ineffective family planning method and of only moderate effectiveness in preventing acquisition of HSV-2 [ 24 ]. Other factors associated with significantly greater probability of HSV-2 seropositivity were having a known HIV-positive partner and being co-infected with HCV.…”
Section: Discussionmentioning
confidence: 99%